2021
DOI: 10.1021/acs.energyfuels.1c02734
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Shale-Oil Recovery during CO2 Huff-n-Puff at Different Pore Scales

Abstract: CO 2 huff-n-puff is an effective technique used in shale-oil reservoirs for supplementing the formation energy and realizing efficient development. This study focuses on typical shale core samples and crude oil. The quantitative evaluation of CO 2 huff-n-puff recovery in shale-oil reservoirs at different pore scales was performed using the nuclear magnetic resonance technology combined with a laboratory physical simulation experiment. The huff-n-puff pressure and soaking time were considered as control variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…During the process of the HnP experiment with online NMR, the main signal detected by the NMR test is the transverse relaxation time ( T 2 ) of 1 H in the oil molecule, and the magnitude of the T 2 response signal can indicate the relative amount of oil present in a porous medium. , T 2 is affected by three different relaxation mechanisms present in porous media, i.e., free relaxation, surface relaxation, and diffusion relaxation, and T 2 can be calculated by the following equation: , 1 T 2 = 1 T 2 b + 1 T 2 s + 1 T 2 D = 1 T 2 b + ρ 2 S V + D false( G γ TE false) 2 12 where T 2 represents the transverse relaxation time of pore fluid (ms); T 2b is the transverse free relaxation (ms), which is the inherent relaxation property of the fluid; T 2s is the transverse surface relaxation time (ms), which is caused by the interaction between the fluid and the pore surface; T 2D is the diffusive relaxation time (ms), which is connected to the diffusion coefficient of the fluid; ρ 2 is the transverse surface relaxation rate (μm/ms); V is the pore volume (μm 3 ); S is the pore surface area (μm 2 ); D is the free diffusion coefficient of the fluid (μm 2 /ms); γ is the spin to magnetism ratio (Hz/T); and TE is the test echo spacing (ms).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of the HnP experiment with online NMR, the main signal detected by the NMR test is the transverse relaxation time ( T 2 ) of 1 H in the oil molecule, and the magnitude of the T 2 response signal can indicate the relative amount of oil present in a porous medium. , T 2 is affected by three different relaxation mechanisms present in porous media, i.e., free relaxation, surface relaxation, and diffusion relaxation, and T 2 can be calculated by the following equation: , 1 T 2 = 1 T 2 b + 1 T 2 s + 1 T 2 D = 1 T 2 b + ρ 2 S V + D false( G γ TE false) 2 12 where T 2 represents the transverse relaxation time of pore fluid (ms); T 2b is the transverse free relaxation (ms), which is the inherent relaxation property of the fluid; T 2s is the transverse surface relaxation time (ms), which is caused by the interaction between the fluid and the pore surface; T 2D is the diffusive relaxation time (ms), which is connected to the diffusion coefficient of the fluid; ρ 2 is the transverse surface relaxation rate (μm/ms); V is the pore volume (μm 3 ); S is the pore surface area (μm 2 ); D is the free diffusion coefficient of the fluid (μm 2 /ms); γ is the spin to magnetism ratio (Hz/T); and TE is the test echo spacing (ms).…”
Section: Methodsmentioning
confidence: 99%
“…S/V is the specific surface of individual pores, which is inversely proportional to the pore radius and can be expressed by the following equation: , S V = F normals r where r is the pore radius (μm) and F s is the pore dimensionless shape factor.…”
Section: Methodsmentioning
confidence: 99%
“…Under the condition of 120 h soaking time, the recovery of the crude oil in macropores increased with the increase of injection pressure. 34 Through the comparison of long core and short core huff and puff experiments, Wang et al observed that a greater pressure drop rate led to a lower recovery rate. Increasing the soaking time was found to be beneficial for enhancing the oil recovery rate.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al quantitatively evaluated the CO 2 huff and puff recovery of shale oil at different pore scales and different soaking times. Under the condition of 120 h soaking time, the recovery of the crude oil in macropores increased with the increase of injection pressure . Through the comparison of long core and short core huff and puff experiments, Wang et al observed that a greater pressure drop rate led to a lower recovery rate.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has been carried out on the application of gas HnP techniques in tight or shale reservoirs, of which some concern the comparative EOR ability of N 2 and CO 2 HnP. Sheng et al examined the effect of gas composition on the HnP effectiveness in the Bakken reservoir using numerical simulation software, CMG-GEM.…”
Section: Introductionmentioning
confidence: 99%